The role of ecotourism in achieving sustainable tourism An analytical study of the views of a sample of managers in the General Authority for Tourism within the city of Erbil exclusively - رۆژان صباح احمد; ئەسرین رمزي حسن; جبرائيل احمد سمايل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The current research seeks to study the role of ecotourism in the achievement of sustainable tourism: An analytical study of the views of a sample of managers in the General Board for Tourism exclusively within the city of Erbil. Ecotourism as an independent variable based on five dimensions: natural basis, tourist satisfaction, local interest, environmental education, and sustainable environment. Sustainable tourism as a dependent variable based on three dimensions: the economic dimension, the socio-cultural dimension, and the environmental dimension. In order to reach the current research objectives, the analytic descriptive approach were adopted in addressing its variables. The selected managers from the service providers has experience in the field of tourism. The number of managers was 57 and distributed the questionnaire, which was designed as a data collection and analysis tool in the field to identify: 1. The extent to which the members of the research sample understood the importance of ecotourism and sustainable tourism for the region? 2. Levels of respondents' awareness of the role of ecotourism in the achievement of sustainable tourism: An analytic study of the views of a sample of managers in the General Board for Tourism within the city of Erbil exclusively? A default model developed based on a number of key hypotheses that reflects the nature of the relationship and impact between ecotourism and sustainable tourism. A range of statistical methods were used for analysis and identification of results, and through the SPSS-v.-18 software. The current research reached a set of conclusions based on the results, the most important of which are: A - There is a positive relationship with statistical indication between the dimensions of ecotourism combined and individual and sustainable tourism, that is, the management of the Tourist Board in the city of Erbil, when doing business takes into consideration the dimensions of eco-tourism to varying degrees. B- There is a strong moral effect of statistical significance for the dimensions of eco-tourism combined and separately in sustainable tourism. C- The dimension of the local interest is the most prominent dimensions of eco-tourism, which have a significant impact on sustainable tourism in the city of Erbil, according to the views of respondents.The research ended with a set of proposals in line with the conclusions to strengthen the base of this vital sector.